Electrophoretic behavior of charge regulated zwitter ionic buffers in covalently and dynamically coated fused silica capillaries - Medhat A. Al-Ghobashy (Faculty of Pharmacy, Cairo University, 2014)
In this work, the electrophoretic behavior of zwitterionic buffers is investigated in the absence of electroosmotic flow (EOF). Electro mobilization of capillary contents is noted when zwitterionic buffers are employed as the background electrolyte at a pH where the buffering moiety carries a net charge. The bulk flow of capillary contents was demonstrated via monitoring the migration of a neutral marker as well as a free and micellar negatively charged marker and SDS-protein complexes. This electrolyte-driven mobilization (EDM) was investigated in detail using 4-(2-hydroxyethyl)piprazine-1-ethanesulfonic acid (HEPES) buffer over a wide pH range (pH 4.0-8.0). Results confirmed that at a pH where HEPES molecules carry a net negative charge, a bulk flow toward the anode is observed. This was attributed to the migration of HEPES ions toward the anode along with their hydration shells. The relatively large difference in size and solvation number between the ionic buffering moiety and its counter-migrating ions (Na+ or H+) resulted in such a net movement. Results indicated that at constant voltage, plotting the measured current versus buffer pH can be used for determination of the isoelectric point of the zwitterionic buffering moiety. Furthermore, this novel mobilization modality was demonstrated using five different HEPES analogs over pH range 5.0-8.0. More in depth investigations are required in order to explore the applicability of EDM in coated capillaries of different wall chemistries and dimensions.